Mechanical behavior simulation: NCF/epoxy composite processed by RTM - Monticeli, Francisco Maciel [UNESP]; Daou, David; Dinulović, Mirko; Voorwald, Herman Jacobus Cornelis [UNESP]; Cioffi, Maria Odila Hilário [UNESP] (SAGE Publications, 2019)
Considering aeronautics requirements, academies and industries are developing matrixes and reinforcements with higher mechanical performance. The same occurs with the process where new studies focus on obtaining composites with suitable matrix/reinforcement interface. The use of epoxy resin and carbon fiber with high mechanical performance does not guarantee a composite with high mechanical properties, considering imperfections and void formation along the laminate in case of inappropriate processing parameters. The aim of this article was to analyze and quantify the mechanical behavior of polymer composite reinforced with continuous fibers using finite element methodology and postprocessing software simulation. In addition, the classical laminate theory and finite elements were used to simulate flexural and tensile tests of composite specimens. Simulation results were compared with experimental test results using a carbon fiber noncrimp fabric quadriaxial/epoxy resin composite processed by resin transfer molding. Although void volume fraction for structural materials presenting results under aeronautics requirements regarding of 2%, imperfections like lack of resin and impregnation discontinuity showed an influence in tensile and flexural experimental results. Experimental mechanical behavior decreased 10% of strength, in comparison with simulation results due to imperfection on impregnation measured by C-Scan map. Improvement in processing procedures could able to provide greater impregnation continuity, reducing defect formation and ensuring better matrix/reinforcement interface. As a final conclusion, the process plays a role as important as the characteristics of reinforcement and matrix and, consequently, the mechanical properties.
Keywords: finite element analysis (FEA); mechanical behavior; Polymer composite; porosity